Planning issues of the yearly cycle of training swimmers - Moshkina, N. A. (The Russian Journal of Physical Education and Sport, 2019)
During recent decades people try to define the preconditions for a successful planning of a training macrocycle in different kinds of sport. They take into account the fact that there are different kinds of planning in practical use. The article presents the author`s approach to planning sports training of swimmers taking into account real conditions, which an athlete and his coach face. The difficulties in training athletes increase with their transfer from stage to stage during a long-term training. Materials. The article is about the questions of planning training among young athletes. While planning training process nowadays specialists take into account the standards of different kinds of sport, where they find the algorithm of actions. The effectiveness of the programs and methodologies is defined after athletes` results estimation. Research methods. Information sources analysis and summarizing, documents and program material study in "Swimming". The scheme of actions is created in planning training swimmers. It takes into account the demands of the traditional approach to planning. Results. We analyzed scientific-methodical literature. We created a block-scheme of planning the process of training swimmers. For the successful training process planning it is necessary to plan the sequence of actions, in order to move in one direction. Generally adopted rules of planning are presented in the variant of general specialist`s actions characteristics. Two directions of planning are created. They include different variants: basic developing, basic accumulating (summary, fundamental) and final-realizable (resultative) mesocycles of training swimmers. Conclusion. Planning repeated mesocycles helps to avoid monotony. It make the process of training swimmers more emotional and interesting. Adaptation to changing physical loads helps to develop coordinated character of actions. The duration of mesocycles should be from 2 to 3-4 weeks. Directed toward physical qualities development long-term physical loads replacement helps to increase the concentration of the training influence. It takes into account the typology of swimmers.